Three-dimensional MRI sequences in MS diagnosis and research. (November 2019) - Hu, Xun Yang; Rajendran, Luckshi; Lapointe, Emmanuelle; Tam, Roger; Li, David; Traboulsee, Anthony; Rauscher, Alexander
The most recent guidelines for magnetic resonance imaging (MRI) in multiple sclerosis (MS) recommend three-dimensional (3D) MRI sequences over their two-dimensional (2D) counterparts. This development has been made possible by advances in MRI scanner hardware and software. In this article, we review the 3D versions of conventional sequences, including T1-weighted, T2-weighted and fluid-attenuated inversion recovery (FLAIR), as well as more advanced scans, including double inversion recovery (DIR), FLAIR 2, FLAIR*, phase-sensitive inversion recovery, and susceptibility weighted imaging (SWI).